Identifikasi dan Karakterisasi Mikoriza pada Tegakan Nyatoh (Palaquium sp.) - Kurnia Kurnia; Gusmiaty Gusmiaty; Siti Halimah Larekeng (PERENNIAL, 2019)
This research aimed to identify the mycorrhiza types that associated in roots and soil on  Palaquium sp. plant. This  research has implemented on December 2017 until February 2018. This research procedures made by two stages includes collecting soil and root samples on Palaquium sp plant on  Ko'mara Community Forest, Takalar District. Therefore, the second step is isolation, identification, and observing colonization of mycorrhiza spores in the Integrated Laboratory and Biotechnology and Tree Breeding Laboratory, Faculty of Forestry, Hasanuddin University, Makassar. The results showed types of spore that found were Glomus, Gigaspora and Acaulospora. Glomus spore has highest relative abundance in root samples whereas on soil samples were Glomus, Gigaspora, and Schleroderma with Glomus spores has highest relative abundance in. The colonization percentage on site was intermediate.